A gestão da informação entre setores administrativos da Reitoria da Universidade Federal da Paraíba e sua contribuição nas tomadas de decisão - Mota, Débora Espínola Fernandes da (2022)
In the last decades of the 20th century and the beginning of the 21st century, there was an accelerated growth of technological and scientific production that promoted the creation of new technologies in the most diverse areas, among which the fields of information and communication stand out. In this context, the information and knowledge society emerged, which, within the scope of public policies, increasingly requires efficient and effective public management. Given this, information management can be used by the public university administration to develop skills that help it to face frequent transformations and external demands, as well as to support managers in the decision-making process, through useful, opportune, and timely information. Based on this premise, this study aimed to investigate the information management process between three administrative sectors that are part of the Rectory of the Federal University of Paraíba and its contribution to managers in the decision making process, using the information management model presented by Choo (2003). Concerning methodological procedures, this research is characterized as being of an applied nature, with a qualitative approach, being descriptive in terms of objectives. For its foundation, bibliographic research was carried out on information management, contemplating renowned authors and specialists in the subject, such as McGee and Prusak (1994), Davenport and Prusak (1998), and Choo (2003). Documentary research was also carried out, proceeding to the analysis of official and institutional documents of the Federal University of Paraíba. As a data collection instrument, semi-structured interviews were used with the managers and coordinators of the selected sectors for the research, using the content analysis technique to analyze the collected data. As a result, a diagnosis of information management in the investigated sectors was traced using SWOT analysis, as well as the design of a manual of routines for information management, containing the development of the information cycle of the researched sectors, aimed at the use of managers in the decision-making process, to enable the implementation of improvements in management and in the sharing of information that contribute to managers in their decision-making in the future.